Estimation of Marbling Score by Ultrasonography and Visual Methods of Male Bali Beef Based on Muscle Location and Storage Time - Abrori, Muh. Muazdzamzam Lil; Bulkaini, Bulkaini; Hasma, Hasma; Kisworo, Djoko; Fahrullah, Fahrullah; Nazir, Novizar; Muhammad Ashari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Marbling refers to white fat granules within muscle fibres that enhance meat tenderness and flavour. This study aimed to determine the marbling score of male Bali beef using two methods: ultrasonography and visual assessment based on muscle location and storage duration. Five intensively raised male Bali cattle (average weight 227 kg) were examined. Visual assessment used 0.5 kg samples from sirloin, rib, and round muscles, analysed with ImageJ and Minitab 17. Results showed that both muscle location and storage duration significantly affected (P < 0.01) the marbling score. The ultrasonography method yielded marbling scores of 1.06–1.44, while the visual method produced 1.10–1.50. The ultrasonography method proved reliable for predicting marbling without slaughter, with higher marbling observed in passive muscles (sirloin) than in active muscles (rib and round). Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero Hunger SDG 9: Industry, Innovation, and Infrastructure SDG 12: Responsible Consumption and Production SDG 15: Life on Land